Editorial. (December 2014) - Alderman, Lyn; Clinton, Janet; Harvey, Graeme
Welcome all members and readers to the second online issue of the Evaluation Journal of Australasia (EJA) for 2014. EJA is a flagship initiative of the Australasian Evaluation Society (AES) whose mission is to build capacity in evaluators across our region. EJA plays an essential part in this task and from 2015 will be published four times a year. At this time, the Editors would like to acknowledge the fantastic work that members and others contribute to the publication of EJA as well as the annual conference and national workshops, which work in a symbiotic relationship to advocate, disseminate and recognise good theory and practice in evaluation.